*Since the x-variables are isolate > set the equation to equal each other...
4y + 5 = 3y - 2
Sec: subtract "5" from both sides...
4y + 5 - 5 = 3y - 2 - 5
4y = 3y - 7
Third: subtract "3y" from both sides...
4y - 3y = 3y - 3y - 7
y = - 7
Fourth: replace "-7" with the y-variable in either equation, let's use the 1st equation...
x = 4(-7) + 5
x = - 28 + 5
x = - 23
Solution: (-23, -7)
2007-01-28 13:09:25
·
answer #1
·
answered by ♪♥Annie♥♪ 6
·
1⤊
0⤋
Quick method. Note that the x's do not different numbers in front. In fact, it is 1.
Thus, you can just equate the 2 given equations to solve for y. (this is basically SUBSTITUTION method)
4y + 5 = 3y -2 Combining like terms and doing the algebra gives you 4y -3y = -2 -5 (Please note the way combining was done so that you have a positive coefficient for y)
Or y = -7.
To solve for x just substitute the y value to either equation
Again for quicker method, use the easier equation. In this case they are both easy but it is a little easy using smaller numbers. So,
x= 3(-7) -2 = -21 -2 = -23
2007-01-28 21:12:31
·
answer #2
·
answered by Aldo 5
·
0⤊
0⤋
Easy. Substitute the 1st equation into the second for the value of x and you get:
4y+5=3y-2.
Solve for y: y=(-7)
Then plug (-7) into either of the original equations to get x:
x=4(-7)+5=(-23) or x=3(-7)-2=(-23)
There you go, x=(-23) and y=(-7). All solved.
2007-01-28 21:07:58
·
answer #3
·
answered by bobo383 3
·
1⤊
0⤋
ok....
you know 4y + 5 equals x.
you also know that 3y - 2 equals x.
THEY BOTH EQUAL THE SAME THING! Yay!
hence you can say 4y+5 = 3y-2 and solve for y. once you have that, plug into either equation to get x!
(the other way to do it is to put the equations one on top of the other and subtract them... you will get 0 on the x side and y+7 on the other. hence 0=y+7., then solve for y... again plug your answer for y into EITHER equation to find x!) :-)
2007-01-28 21:11:19
·
answer #4
·
answered by hp-answers.yahoo 3
·
1⤊
0⤋
x=4y+5 and x=3y-2?
4y+5=3y-2 [Both = x so must = each other]
4y-3y = -2-5
y = -7
x = 4y+5 = 4(-7) +5 = -28+5 = -23
2007-01-28 21:07:50
·
answer #5
·
answered by ironduke8159 7
·
1⤊
0⤋
x=4y+5
x=3y-2
Two eq are equal therefore
4y+5=3y-2
4y-3y=-2-5
y= -7
x=4(-7)+5
= -23
2007-01-28 21:30:13
·
answer #6
·
answered by flying_phoenix 2
·
0⤊
0⤋
both equal x so
4y+5=3y-2
-5 -5
4y=3y-2-5
4y=3y-7
-3y -3y
1y= -7
or y = -7
then substitute -7 for y in one of the other equations
x=4(-7) + 5
x= -28+5
x= -23
2007-01-28 21:11:21
·
answer #7
·
answered by katelle 2
·
1⤊
0⤋
x=4y+5
x=3y-2 subtract
0=y+7 subtract 7 from each side
y=-7
x=4*(-7)+5
x=-28+5
x=-23
(-23, -7)
check
3*(-7)-2=-21-2=-23=x
2007-01-28 21:04:36
·
answer #8
·
answered by yupchagee 7
·
1⤊
1⤋
Plug 3y-2 in for x in the first equation. Solve for y, then plug that into either equation and solve for x.
2007-01-28 21:05:24
·
answer #9
·
answered by koyaanisqatsi12 2
·
1⤊
2⤋
4y+5=3y-2
4y-3y=-5-2
y=-7
x=4(-7)+5
x=-23
2007-01-28 21:18:04
·
answer #10
·
answered by lost 2
·
0⤊
0⤋